Electrospinning of nonwoven aerogel-polyethene terephthalate composite fiber mats by pneumatic transport. (July 2019) - Christiansen, Lasse; Jensen, Lars R; Fojan, Peter
The use of fiber materials includes construction-, automotive-, textile industry, to filters for water and air cleaning as well as hydroponic growth media. Different applications demand different fiber types and properties. This study presents a new production method for a composite fiber material composed of a dry aerogel particle and a polymer. The production method combines the electrospinning process with pneumatic transport of aerogel particles and creates aerogel–polymer composite fibers. The fibers are characterised through scanning electron microscopy, thermogravimetric analysis and tensile testing. They are compared to reference fibers made of pure polymer. The experiments yielded an aerogel–polymer composite fiber material, which contained aerogel particles. This fiber material did not contain excess solvent, and supported the aerogel particles. The strain to failure and the maximum force per weight were found to be lower for the aerogel–polymer composite fibers compared to reference fibers without aerogel.